The evolution and genetic control of stress tolerance in a complex world - Everman, Elizabeth R. (Kansas State University, 2017)
Natural populations are highly complex and consist of genetically variable individuals that belong to continuously varying age classes. Genotype and age interact to determine how individuals respond to environmental stress, which ultimately determines the evolutionary trajectories and persistence of populations in variable environments. For small ectothermic species, seasonal and diurnal variation in temperature is an important source of environmental stress that impacts activity patterns and suites of phenotypes directly related to whole organism fitness. I used the genetic and ecological model Drosophila melanogaster to investigate the influence of seasonal and diurnal thermal variability on survival and reproduction in genetically diverse populations. First, I characterized changes in cold tolerance and phenotypic plasticity within a natural population as it responded to seasonal shifts in developmental and short-term acclimation and thermal selection. I found that seasonal variation in cold tolerance was significantly influenced by developmental acclimation that occurred in the field as well as in the lab, where flies that developed under warmer conditions had reduced cold tolerance relative to flies that developed under cooler conditions. Second, I characterized the effect of variation in age on stress response phenotypes in a genetically variable population. I measured genotype- and age-specific responses to multiple environmental stressors, and identified regions of the genome that were associated with age-specific stress tolerance. Genome-wide association mapping revealed that age-specific phenotypes were influenced by distinct sets of polymorphisms and genes, suggesting that the evolution of age-related decline in phenotypes is driven by mutation accumulation within phenotypes, but both mutation accumulation and antagonistic pleiotropy between phenotypes. Next, I characterized the costs and benefits of acclimation for survival and reproduction to understand how physiological and behavioral plasticity interact to determine fitness. I found that phenotypic plasticity and the capacity for acclimation significantly influenced behavioral reproductive success, but the thermal cues that led to adaptive acclimation response in survival also led to decreased reproductive success. However, genotypes with the capacity to acclimate were more likely to survive thermal variation and more likely to reproduce, suggesting that genetic capacity for phenotypic plasticity has important implications for whole organism fitness. Finally, I measured the effect of acclimation on the induction of diapause and ability to survive cold stress in the recently introduced invasive species Drosophila suzukii. D. suzukii is endemic to Asia and was first detected in California in 2008 and in Topeka, KS in 2013. Its recent invasion history thus provides an interesting model to understand the role of plasiticy in the response to a novel and variable environment. I found that diapause was induced through a plastic response to acclimation and short photoperiod, though diapause was more drastically induced by acclimation. Overall, my research provides critical insights into how organisms respond to thermal variation by intergrating quantitative genetics, ecology, evolution, and life history tradeoffs. Collectively, my research demonstrates that the ability of organisms to survive thermal stress is a function of genetic capacity to tolerate stress, genetic capacity for phenotypic plasticity, prior exposure to thermal variation, and the age of the individual.
Keywords: Seasonality; Aging; Drosophila Genetic Reference Panel; Mating behavior; Invasive species; Fitness